2016
DOI: 10.1007/s10896-016-9883-2
|View full text |Cite|
|
Sign up to set email alerts
|

The Social Construction of Roles in Intimate Partner Violence: Is the Victim/Perpetrator Model the only Viable one?

Abstract: This article addresses controversies in the field over LGBTQ intimate partner violence by describing the scope of the problem, employing both the traditional feminist paradigm and poststructuralist feminist theoretical approach to frame the problem, and, lastly, provide suggestions for advancing the field using interdisciplinary theories and methods. Implications for the field, policy, and treatment of victims and perpetrators of LGBTQ intimate partner violence are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Mediation is one such context and stories about IPV and coercive control in relationships are, now, highly resonant in mediations. The traditional understanding of IPV that asserts men are the abusers and women are the victims (Cannon and Buttell, 2016) has, importantly, been nuanced in both research studies and in mediators’ understandings of violence, as our data suggest, to recognize all forms of victimization. However, the neutrality and impartiality required by mediator codes may require ignoring or rejecting feminist understandings of underlying gendered social power rooted in patterns of gendered labor that can also matter in mediations (Bollen et al , 2013), both in addition to and concurrent with experiences of IPV.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Mediation is one such context and stories about IPV and coercive control in relationships are, now, highly resonant in mediations. The traditional understanding of IPV that asserts men are the abusers and women are the victims (Cannon and Buttell, 2016) has, importantly, been nuanced in both research studies and in mediators’ understandings of violence, as our data suggest, to recognize all forms of victimization. However, the neutrality and impartiality required by mediator codes may require ignoring or rejecting feminist understandings of underlying gendered social power rooted in patterns of gendered labor that can also matter in mediations (Bollen et al , 2013), both in addition to and concurrent with experiences of IPV.…”
Section: Discussionmentioning
confidence: 79%
“…Instead, invoking a poststructuralist feminist critique, we recognize that gender intersects with power and violence in ways affected by privilege. Such enactments are then interpreted by others such as mediators, through the lens of a gendered hierarchy (Cannon and Buttell, 2016). Acknowledging those interpretations and their effects and improving systems such as mediation where those interpretations are vital to equitable resolutions, are important feminist strategies for social justice (Kelly, 2011).…”
Section: Family Law Mediationmentioning
confidence: 99%
See 1 more Smart Citation
“…This discourse of males-as-perpetrators and females-as-victims has expressed and reflected dominant social hierarchies of White, heterosexual men at the top of the social pyramid, with, for instance, queer-identified women of color at the bottom of the hierarchy. However, recent scholarship (e.g., Cannon & Buttell, 2015, 2016) has begun to challenge this patriarchal analysis of IPV by arguing that the men-as-perpetrator and females-as-victim paradigm does not reflect female perpetrators or lesbian gay bisexual transgendered queer perpetrators. These studies have pointed out that White culture, as the dominant one in the United States, has defined what an IPV perpetrator and victim looks like.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies using the social construction theory of violence have placed the discussions between the two poles of a dyad, that is, the perpetrator and the victim dyad. On the perpetrator side, researchers have focused on the justification for and circumstances of violence by perpetrators and the impact of violence on victims' well-being (Bosco, Schneider, Coleston-Shields, Higgs, & Orrell, 2019;Cannon & Buttell, 2016;Dalton, Jung, & Willis, 2017;Kaye, Mirembe, Ekstrom, Bantebya, & Johansson, 2005;Mehrotra, 1999;Muehlenhard & Kimes, 1999;Salter, 2016). On this side of the dyad, studies have examined perpetrators' construction of violence, which is founded on hegemonic masculinity, and concluded that manliness is associated with assertiveness, aggressiveness, independence, dominance, and violence (Bhana & Mayeza, 2016;Bozkurt, Tartanoglu, & Dawes, 2015;Taylor, das Nair, & Braham, 2013).…”
Section: Introductionmentioning
confidence: 99%